An effective technique of helical cartilage scoring for correction of prominent ear deformity - Ashok Raj Koul; Rahul K Patil (Indian Journal of Plastic Surgery)
Otoplasty has a long history starting from 1948, when Dieffenbach described it first. Multiple technical modifications have been reported since. We propose a technique of scoring the helical cartilage without a visible incision on the lateral aspect of pinna for easier remolding of cartilage through posterior approach. The results have been excellent.